2021
DOI: 10.1016/j.physio.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and benefits of a structured prehabilitation programme prior to autologous stem cell transplantation (ASCT) in patients with myeloma; a prospective feasibility study

Abstract: Evidence supports the benefits of exercise-based rehabilitation in promoting recovery in myeloma patients following autologous stem-cell transplantation (ASCT). However, 'prehabilitation' has never been evaluated prior to ASCT, despite evidence of effectiveness in other cancers. Utilising a mixed method approach the authors investigated the feasibility of a mixed strength and cardiovascular exercise intervention pre-ASCT. Quantitative data were collected to determine feasibility targets; rates of recruitment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Allowance for these accommodations allows exercise to fit the patient's lifestyle, rather than making a patient's lifestyle fit the exercise program, mimicking "real world" exercise habits. Further, there were zero intervention-related adverse or serious adverse events, consistent with previous trials investigating pre-HSCT exercise, regardless of transplant and hematologic malignancy type [28][29][30]32,33]. This further supports the assertion that if exercise is pragmatically programed and prescribed to accommodate the patients clinicopathologic history while also targeting functional improvements, exercise is safe to be performed unsupervised for a large proportion of AUTO and ALLO HSCT recipients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Allowance for these accommodations allows exercise to fit the patient's lifestyle, rather than making a patient's lifestyle fit the exercise program, mimicking "real world" exercise habits. Further, there were zero intervention-related adverse or serious adverse events, consistent with previous trials investigating pre-HSCT exercise, regardless of transplant and hematologic malignancy type [28][29][30]32,33]. This further supports the assertion that if exercise is pragmatically programed and prescribed to accommodate the patients clinicopathologic history while also targeting functional improvements, exercise is safe to be performed unsupervised for a large proportion of AUTO and ALLO HSCT recipients.…”
Section: Discussionsupporting
confidence: 84%
“…Exercise adherence in our trial was high (91.98%, range: 33-190%), regardless of transplant. Previous reports of exercise adherence have ranged from 55% to 99% [29][30][31][32][33], while other trials were unable to report on exercise adherence due to failure of study participants to return exercise logs [28]. The high exercise adherence rate seen in this trial could be attributed to the pragmatic design of the exercise program.…”
Section: Discussionmentioning
confidence: 64%
“…The trials by van Haren et al and Rupnik et al are non-randomised feasibility trials, which do not allow for comparison to a non-exercising group 27 28. In addition, the PREeMPT trial,29 the PERCEPT trial30 and the feasibility trial by Mawson et al 31 focus on patients diagnosed with multiple myeloma who are receiving an AUTO transplant, while Wood et al 32 used only aerobic exercise for ALLO patients. Finally, the trials completed by Wiskemann et al 33 and Santa Mina et al 34 included exercise for ALLO patients during multiple phases of the transplant process, making it more difficult to discern the impact of the pretransplant exercise intervention.…”
Section: Introductionmentioning
confidence: 99%
“…It supports patients to prepare for treatment by promoting healthy behaviours and needs-based prescribing of exercise, nutrition and psychological interventions [7]. There is emerging evidence to support cancer prehabilitation prior to AuSCT, with studies reporting that it is safe and feasible [8,9] and may mitigate the decline in functional exercise capacity, muscle strength and HRQoL that is experienced prior to and during AuSCT [10][11][12]. However, feasibility and observational studies reported issues with acceptability, attrition, data collection and intervention delivery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research in cancer prehabilitation primarily focuses on the patient experience or barriers to implementation [13][14][15]. Although there are reported di culties delivering prehabilitation prior to AuSCT [11,12], there is a gap in current literature regarding clinicians' perceptions of enablers and barriers to prehabilitation delivery.…”
Section: Introductionmentioning
confidence: 99%